Raffaele Pettazzoni e le religioni indiane - Scialpi, Fabio (Studi e materiali di storia delle religioni, 2011)
The article focuses on the study of Indian religions by Raffaele Pettazzoni considering two distinct planes, phenomenology and religious history.